Program Jumat Berkah dalam Meningkatkan Nilai-Nilai Pendidikan Agama Islam - Lestari, Sindi; Harfiani, Rizka (Hikmah, 2023)
The values of Islamic education are things that must be owned and applied to students. There are many ways to obtain these values, including through the Friday Blessing program. In this regard, this study aims to analyze the application of the Friday Blessing program in improving the values of Islamic Religious Education for students. This research uses a qualitative method with a phenomenological approach. Data collection techniques were conducted through interviews, observation, and documentation, with the research subjects being the principal, teachers, and students. This research was conducted at SMK Swasta Mandiri in Panai Hulu, Labuhan Batu, North Sumatra. The data analysis technique used descriptive methods to describe the implementation of the Friday Blessing program in improving Islamic Religious Education values. The results showed that the implementation of the Friday Blessing program at SMK Swasta Mandiri is carried out twice a week, the donations given are in the form of money and staples. The implementation technique is that students visit the residence of the recipient of the donation accompanied by the teacher of SMK Swasta Mandiri, this intends to foster the social spirit and generosity of students in giving alms, which is part of the learning values of Islamic Religious Education. With this research, it is hoped that it can provide and be able to improve the values of Islamic religious education for students and have a positive impact on the surrounding community.